PENGARUH PERCEIVED EASE OF USE, PERCEIVED SECURITY, DAN CUSTOMER SATISFACTION TERHADAP REPURCHASE INTENTION GUNA MENINGKATKAN PANGSA PASAR - RICKY YOHANES; NUNO SUTRISNO (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
The purpose of this study is to analyze and examine the influence of perceived ease of use, perceived security, and customer satisfaction toward repurchase intention on Acer website users who do purchase laptop product in DKI Jakarta. The research form used in this study is descriptive and causal research, using five points of likert scale to measure all variables. Sample collected using purposive sampling technique with primary and secondary data and using 144 respondents. Data analytic method using in this study is multiple linear regression with IBM SPSS 25 statistical test tools. The result of this research has shown that perceived ease of use, perceived security, and customer satisfaction have an effect on repurchase intention to Acer website users who do purchase laptop product in DKI Jakarta.